W+ W- boson pair production in proton-proton collisions at root s=13 TeV - Sirunyan,AM; Tumasyan,A; Adam,W; Ambrogi,F; Bergauer,T; Dragicevic,M; Ero,J; Del,Valle AE; Flechl,M; Fruhwirth,R; Jeitler,M; Kratschmer,I; et al. (Physical Review D: Particles, Fields, Gravitation and Cosmology, 2020)
A measurement of the W+W− boson pair production cross section in proton-proton collisions at √s=13  TeV is presented. The data used in this study are collected with the CMS detector at the CERN LHC and correspond to an integrated luminosity of 35.9  fb−1. The W+W− candidate events are selected by requiring two oppositely charged leptons (electrons or muons). Two methods for reducing background contributions are employed. In the first one, a sequence of requirements on kinematic quantities is applied allowing a measurement of the total production cross section, 117.6±6.8  pb, which agrees well with the theoretical prediction. Fiducial cross sections are also reported for events with zero or one jet, and the change in the zero-jet fiducial cross section with the jet transverse momentum threshold is measured. Normalized differential cross sections are reported within the fiducial region. A second method for suppressing background contributions employs two random forest classifiers. The analysis based on this method includes a measurement of the total production cross section and also a measurement of the normalized jet multiplicity distribution in W+W− events. Finally, a dilepton invariant mass distribution is used to probe for physics beyond the standard model in the context of an effective field theory, and constraints on the presence of dimension-6 operators are derived.